2012
DOI: 10.1074/jbc.m112.395053
|View full text |Cite
|
Sign up to set email alerts
|

A Conformational Change of the γ Subunit Indirectly Regulates the Activity of Cyanobacterial F1-ATPase

Abstract: Background: A conformational change of the ␥ subunit of ATP synthase may be critical for enzyme regulation. Results: A conformational change of ␥ controls both ADP inhibition and ⑀ inhibition. Conclusion: The ␥ subunit indirectly regulates the activity by way of ADP inhibition and ⑀ inhibition. Significance: Regulation system of ATP synthase based on the unique molecular structure of the ␥ subunit was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…9), an interaction with βI397 was not required for changed ADP inhibition and redox regulation upon mutation. Some contradictions in our study might be attributed to an additional parameter that was described recently and could play a role in the CF 1 -ATPase redox regulation in general [32]. Therein, the authors demonstrated that restricting relative slippage of the γ-termini diminishes ADP inhibition.…”
Section: F 1-redox Mutant Enzyme Effect On Atpase Redox Regulationcontrasting
confidence: 57%
See 2 more Smart Citations
“…9), an interaction with βI397 was not required for changed ADP inhibition and redox regulation upon mutation. Some contradictions in our study might be attributed to an additional parameter that was described recently and could play a role in the CF 1 -ATPase redox regulation in general [32]. Therein, the authors demonstrated that restricting relative slippage of the γ-termini diminishes ADP inhibition.…”
Section: F 1-redox Mutant Enzyme Effect On Atpase Redox Regulationcontrasting
confidence: 57%
“…The methods applied here were slightly modified from previous reports [30,32]. The complex was purified from E. coli cell extracts in Buffer A, which contained 20 mM HEPES-KOH (pH 8.0), 100 mM KCl, 0.1 mM MgCl 2 , 0.1 mM ADP, and 50 mM imidazole.…”
Section: Expression and Purification Of The α 3 β 3 γ Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of both the plastid and mitochondrial ATP synthases has been studied extensively (Hamasur and Glaser, 1992;Yoshida et al, 2001;Sunamura et al, 2012). We have shown previously that the subunits from both complexes turn over at comparable rates in Arabidopsis cell culture .…”
Section: Atp Synthasesmentioning
confidence: 99%
“…These values are comparable with those of other inhibited bacterial F-ATPases where no inhibitor protein is involved. For example, the values for the F 1 -ATPase from the cyanobacterium Thermosynechococcus elongatus are 0.2 and 9.0 U per milligram of protein before and after activation with LDAO (Sunamura et al, 2012). For C. thermarum they are 0.9 and 28.5 U per milligram of protein before and after activation (Keis et al, 2006), and for the chloroplast F 1 -ATPase from Spinacia oleracea they are 4.4 and 39.7 U per milligram of protein before and after activation (Groth & Schirwitz, 1999).…”
Section: Resultsmentioning
confidence: 99%